Variants in ADIPOQ gene are linked to adiponectin levels and lung function in young males independent of obesity - Christodoulou, Andria; Ierodiakonou, Despo; Awofala, Awoyemi Abayomi; Petrou, Michael; Kales, Stefanos N.; Christiani, David C.; Mantzoros, Christos S.; Christophi, Costas A. (My University, 2020)
Background Obesity is a major risk factor for many chronic diseases, including reduced lung function. The role of polymorphisms of the adiponectin gene, though linked with cardiometabolic consequences of obesity, has not been studied in relation to lung function. Objectives The aim of this study is to examine polymorphisms in the ADIPOQ, ADIPOR1, and ADIPOR2 genes in relation to adiponectin serum levels, BMI, and adiposity in 18-year old Cypriot males, as well as determine whether BMI, adipokines levels and polymorphisms in adipokine related genes are associated with lung function levels. Results From the participants, 8% were classified as obese, 22% as overweight, and the remaining 71% as normal. We found that rs266729 and rs1501299 in ADIPOQ and rs10920531 in ADIPOR1 were significantly associated with serum adiponectin levels, after adjusting for ever smoking. In addition, there was an overall significant increase in FEV1%predicted with increasing BMI (β = 0.53, 95% CI: 0.27, 0.78) and in FVC %predicted (β = 1.02, 95% CI: 0.73, 1.30). There was also a decrease in FEV1/FVC with increasing BMI (β = -0.53, 95% CI: -0.71, -0.35). Finally, rs1501299 was associated with lung function measures. Discussion Functional variants in the ADIPOQ gene were linked with lung function in young males. Further studies should concentrate on the role of adipokines on lung function which may direct novel therapeutic approaches.
Keywords: Adiponectin Receptors; AdipoRon; Hypoadiponectinemia